Intrapreneurial Self-Capital: A Primary Preventive Resource for Twenty-First Century Entrepreneurial Contexts - Di Fabio, Annamaria; Duradoni, Mirko (Frontiers in Psychology, 2019)
This article discusses the role of intrapreneurial self-capital (ISC) as a possible primary preventive resource to effectively deal with the complexity of the current entrepreneurial environment. The article deepens both the similarities and differences between ISC and psychological capital and thus proceeds to present the most recent empirical evidence that connects ISC to (1) employability and career decision making, (2) innovative behavior, and (3) well-being. The possibilities for further research and interventions are additionally discussed.